Non-Suicidal Self-Injury, Impulsivity, and Addiction to Social Networks and the Internet in Adolescents - Carretero, Eva M.; López-Martínez, Luis-Fernando; Pérez-García, Ana M.; Carrasco, Miguel Á. (Anales de Psicología / Annals of Psychology, 2024)
Impulsivity and addiction to social networks and the internet are two important risk factors associated with non-suicidal self-injury (NSSI) in adolescents. This quantitative, cross-sectional study explored the specific relationships between these constructs, giving consideration to the influence of sex. For this purpose, the Functional Self-Report Assessment of Self-Mutilation Scale (FASM) was used to assess NSSI, the Internet and Social Network Addiction Risk Scale for Adolescents (ERAR-SI) to measure digital addiction, and the Barratt Impulsivity Scale (BIS-11) to analyze impulsivity. The sample consisted of 516 participants (49.2% of whom were female) aged 11–21 years old. Several statistical analyses were conducted, including calculation of the sample’s main descriptive statistics, correlations, hierarchical logistic regression and structural equation analyses (path analysis and multigroup analysis). The results indicate significant relationships between NSSI and impulsivity and digital addiction and between NSSI and age and sex, with motor impulsivity, freaky behaviors and female sex being significant predictor variables. Although this study has certain limitations, these findings highlight the relevance of gender to self-injurious behavior and provide valuable information that can be used to develop specific NSSI interventions aimed at adolescents.